Ultrathin epitaxial NbNx film deposited by PEALD method on C-plane sapphire: Growth, structure and superconducting properties - Shibalov, M.V.; Sirotina, A.P.; Pershina, E.A.; Martovitskii, V.P.; Shibalova, A.A.; Mumlyakov, A.M.; Trofimov, I.V.; Timofeeva, E.R.; Porokhov, N.V.; Zenova, E.V.; Tarkhov, M.A. (Applied surface science, 2023)
Here we report on the results of obtaining and study of epitaxial ultrathin superconductive films of niobium nitride (NbNx) grown on a C-plane sapphire substrate. The films were deposited from the TBTDEN metal-organic precursor using the plasma-enhanced atomic layer deposition (PEALD) technique at 350 °C and NH3/Ar and H2/Ar gas mixtures as reactants. We employed X-ray diffraction (XRD), X-ray reflectometry (XRR), and high-resolution transmission electron microscopy (HRTEM) techniques to study the structural properties of the films. The investigation demonstrated that NbN layers grow in the plane (111) and consist of twins which axes 11¯0 are parallel to the substrate axes 11¯00 in the basal plane. The cubic lattice of layers is subject to rhombohedral deformation involving distortion of right angles up to 89° due to the four NbNx lattices coincide with the three sapphire lattices with misfit of 0.31%. We have also determined the quasiparticle diffusion constant and the coherence length of the NbNx films. The values of superconducting transition temperature and critical current density were determined as 12 K and 6.2 МА/cm2, respectively. [Display omitted] •Ultrathin superconducting niobium nitride epitaxial films were obtained by plasma- enhanced atomic layer deposition at 350°.•The investigation demonstrated that NbNx layers grow in the plane (111) and consist of twins which axes 11¯0 are parallel to the substrate axes 11¯00 in the basal plane.•The film is homogeneous in thickness and has a coherent film-substrate interface.•The cubic lattice of layers is subject to rhombohedral deformation involving distortion of right angles up to 89° due to the four NbNx lattices coincide with the three sapphire lattices with misfit of 0.52%.•Superconducting properties of fabricated NbNx films.